Charge Carrier Diffusion Dynamics in Multisized Quaternary Alkylammonium-Capped CsPbBr 3 Perovskite Nanocrystal Solids - Gutiérrez Álvarez, Sol; Lin, Weihua; Abdellah, Mohamed; Meng, Jie; Žídek, Karel; Pullerits, Tõnu; Zheng, Kaibo (ACS applied materials & interfaces, 2021)
CsPbBr quantum dots (QDs) are promising candidates for optoelectronic devices. The substitution of oleic acid (OA) and oleylamine (OLA) capping agents with a quaternary alkylammonium such as di-dodecyl dimethyl ammonium bromide (DDAB) has shown an increase in external quantum efficiency (EQE) from 0.19% (OA/OLA) to 13.4% (DDAB) in LED devices. The device performance significantly depends on both the diffusion length and the mobility of photoexcited charge carriers in QD solids. Therefore, we investigated the charge carrier transport dynamics in DDAB-capped CsPbBr QD solids by constructing a bi-sized QD mixture film. Charge carrier diffusion can be monitored by quantitatively varying the ratio between two sizes of QDs, which varies the mean free path of the carriers in each QD cluster. Excited-state dynamics of the QD solids obtained from ultrafast transient absorption spectroscopy reveals that the photogenerated electrons and holes are difficult to diffuse among small-sized QDs (4 nm) due to the strong quantum confinement. On the other hand, both photoinduced electrons and holes in large-sized QDs (10 nm) would diffuse toward the interface with the small-sized QDs, followed by a recombination process. Combining the carrier diffusion study with a Monte Carlo simulation on the QD assembly in the mixture films, we can calculate the diffusion lengths of charge carriers to be ∼239 ± 16 nm in 10 nm CsPbBr QDs and the mobility values of electrons and holes to be 2.1 (± 0.1) and 0.69 (± 0.03) cm /V s, respectively. Both parameters indicate an efficient charge carrier transport in DDAB-capped QD films, which rationalized the perfect performance of their LED device application.